2016
DOI: 10.1016/j.devcel.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Folates Provide an Exogenous Signal for C. elegans Germline Stem Cell Proliferation

Abstract: Summary Here we describe an in vitro primary culture system for C. elegans germline stem cells. This culture system was used to identify a bacterial folate as a positive regulator of germ cell proliferation. Folates are a family of B-complex vitamins that function in one-carbon metabolism to allow the de novo synthesis of amino acids and nucleosides. We show that germ cell proliferation is stimulated by the folate 10-formyl-tetrahydrofolate-Glun both in vitro and in animals. Other folates that can act as vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 55 publications
5
50
0
Order By: Relevance
“…We utilized germ cells isolated from the tumorous mutant glp-1(ar202); cki-2(ok2105); daf-16(mu86) , which contains a gain-of-function (gf) temperature sensitive (ts) glp-1 allele; hereafter referred to as glp-1(gf); cki-2; daf-16 . This strain survives longer in culture than other tested tumorous mutant strains (Chaudhari et al, 2016). We observed that the addition of physiological concentrations of Δ 7 -DA (Motola et al, 2006) had deleterious effects on the isolated germ cells, causing them to die more rapidly with increasing concentration (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…We utilized germ cells isolated from the tumorous mutant glp-1(ar202); cki-2(ok2105); daf-16(mu86) , which contains a gain-of-function (gf) temperature sensitive (ts) glp-1 allele; hereafter referred to as glp-1(gf); cki-2; daf-16 . This strain survives longer in culture than other tested tumorous mutant strains (Chaudhari et al, 2016). We observed that the addition of physiological concentrations of Δ 7 -DA (Motola et al, 2006) had deleterious effects on the isolated germ cells, causing them to die more rapidly with increasing concentration (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…To test the effect of DA on an essentially pure population of germ cells, we utilized an in vitro primary culture system that can maintain viable germ cells from diverse germline tumorous mutants in culture, but without a net increase in germ cell numbers (Chaudhari et al, 2016). We utilized germ cells isolated from the tumorous mutant glp-1(ar202); cki-2(ok2105); daf-16(mu86) , which contains a gain-of-function (gf) temperature sensitive (ts) glp-1 allele; hereafter referred to as glp-1(gf); cki-2; daf-16 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations